THRIFT SHOPING TRENDS IN BUILDING WORD OF MOUTH AND INCREASING SHOPPING INTEREST IN ECOMMERCE SHOPEE - Fitryani Fitryani; Aditya Surya Nanda Aditya Surya Nanda (SEAN Institute, 2022)
This study aims to find out how electronic word of mouth in encouraging thrift shop trends, to find out how electronic word of mouth in improving thrift shop marketing, and to find out how electronic word of mouth in encouraging shopping interest in thrift products. This study uses qualitative research, in order to find out and provide an overview of the problems that are happening, in qualitative research data collection is obtained from facts obtained in the field. The results show that the thrifting trend is influenced by electronic word of mouth, so that people, especially young people interested in buying the product being sold. and with word of mouth as a strategy that benefits sellers, because they don't have to chase the ball, so they can save time and costs. The use of thrift products is considered a contemporary slang which results in continuous purchasing of thrift products. Marketing through e-commerce to sell thrift products is a phenomenon in itself, it is easy to sell products that they cannot sell directly, only based on photo catalogs on ecoomerce though. Reviews and feedback provided by customers are a very important part to encourage increased sales of informants. Interest in shopping for thrift products is related to the purpose of buying, the result of previous eWOM perceived by customers. Economic conditions that occur to buyers, so they buy their own products. Information obtained through eWOM from customer story updates and postings via social media can encourage customers to be interested in buying